1999
DOI: 10.1046/j.1440-1746.1999.01843.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pantoprazole, a novel H+/K+‐ATPase inhibitor, on duodenal ulcerogenic and healing responses in rats: A comparative study with omeprazole and lansoprazole

Abstract: We conclude that pantoprazole exhibited both anti-ulcer and healing promoting effects on duodenal ulcers in rats, and the effects may be attributable to its potent anti-secretory action. Other pump inhibitors such as omeprazole and lansoprazole were almost equally effective as pantoprazole, yet this drug was most potent on the basis of ED50 values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Clinical efficacy and safety studies with pantoprazole (40 mg daily) have consistently shown healing rates for oesophageal erosions of 70–80% following 4 weeks of treatment and of > 80% after 8 weeks. These rates are superior to those obtained with ranitidine, 11–13 and comparable to those for omeprazole 14–16 and lansoprazole 17 ,. 18 Clinical studies have indicated that pantoprazole is effective for the rapid healing of erosive oesophagitis, 19 as well as in relieving symptoms in patients with mild erosive disease 20 ,.…”
Section: Introductionmentioning
confidence: 51%
“…Clinical efficacy and safety studies with pantoprazole (40 mg daily) have consistently shown healing rates for oesophageal erosions of 70–80% following 4 weeks of treatment and of > 80% after 8 weeks. These rates are superior to those obtained with ranitidine, 11–13 and comparable to those for omeprazole 14–16 and lansoprazole 17 ,. 18 Clinical studies have indicated that pantoprazole is effective for the rapid healing of erosive oesophagitis, 19 as well as in relieving symptoms in patients with mild erosive disease 20 ,.…”
Section: Introductionmentioning
confidence: 51%
“…It is of interest to note that the effectiveness of FEMY-R7 at 30 or 100 mg/kg was comparable to that of 30 mg/kg pantoprazole, since it is well known that proton-pump inhibitors such as pantoprazole inhibit gastric secretion [35,36], protect parietal cells [7,37,38], and suppress H. pylori growth [39,40,41]. Compared with the results using CLO kits that detect urease activity, the bacterial cells were detected in more mice (Tables 1 and 2); i.e., the partially-positive stomachs in CLO test revealed H. pylori bacteria in Giemsa-stained mucosa (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…53,[81][82][83] It should be noted that Takeuchi et al 84) reported that portal hypertension significantly inhibited epithelial cell proliferation at the ulcer margins, delaying the healing of acetic acid ulcer in rats. Nonetheless, omeprazole treatment significantly accelerated ulcer healing in both normal rats and rats with portal hypertension to a similar extent.…”
Section: Anti-secretory Drugs H2-blockersmentioning
confidence: 99%